Isolation and Partial Characterization of Flavone from Sudanese Acacia nilotica subsp. adstringens Pods and Antibacterial activity of Pod Fractions - , Mohamed,A.M.; Mayada,I.S.; Weam.A.K. (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2019)
The methanolic extract of Acacia nilotica subsp. adstringens pods was fractionated over silica gel plates to give a flavonoid-compound I . The structure of compound I was partially characterized via some spectral data: UV, 1HNMR . Different fractions of acacia nilotica were assessed for their antimicrobial activity against Gram negative (Escherichia coli and Pseudomonas aeruginos) , Gram positive (Bacillus subtilis and Staphylococcus aureus) and the yeast Candida albicans. The n-butanol and ethanol fractions showed moderate activity against Pseudomonas aeruginosa.The ethyl acetate fraction exhibited moderate activity against Bacillus subtiles while the chloroform fraction showed moderate activity against Bacillus subtilis and Staphylococcus aureus.